Configural and component processing in simultaneous and sequential lineup procedures. Issue 3 (15th March 2016) - Flowe, Heather D.; Smith, Harriet M. J.; Karoğlu, Nilda; Onwuegbusi, Tochukwu O.; Rai, Lovedeep
Abstract : Configural processing supports accurate face recognition, yet it has never been examined within the context of criminal identification lineups. We tested, using the inversion paradigm, the role of configural processing in lineups. Recent research has found that face discrimination accuracy in lineups is better in a simultaneous compared to a sequential lineup procedure. Therefore, we compared configural processing in simultaneous and sequential lineups to examine whether there are differences. We had participants view a crime video, and then they attempted to identify the perpetrator from a simultaneous or sequential lineup. The test faces were presented either upright or inverted, as previous research has shown that inverting test faces disrupts configural processing. The size of the inversion effect for faces was the same across lineup procedures, indicating that configural processing underlies face recognition in both procedures. Discrimination accuracy was comparable across lineup procedures in both the upright and inversion condition. Theoretical implications of the results are discussed.